Jamming Effect Analysis of Two Chinese GNSS BeiDou-II Civil Signals - Jeehyeon Baek; Seungsoo Yoo; Sun Yong Kim (Institute of Advanced Engineering and Science, 2012)
Threats of electronic warfare, especially to global positioning systems (GPSs), have been rapidly increasing. The development of the Chinese navigation satellite system BeiDou has been extended to a global navigation satellite system (GNSS). In December 2011, the Chinese government released a specification document—a test version of a civil BeiDou-II signal called B1(I). A strong possibility exists that BeiDou-II (Chinese GNSS) will be adopted by North Korea in the near future. Therefore, research on BeiDou-II is essential. Since BeiDou-II is a newly-built system, few jamming effect analyses of its positioning signals have been performed. Thus, in this study, we analyze quality factors (Q) and the tolerable jamming signal power among two BeiDou-II civil signals, and two GPS civil signals, in three jamming conditions: band-limited white noise (BLWN), matched spectrum (MS), and continuous wave (CW). In addition, we present each jamming propagation range.DOI:http://dx.doi.org/10.11591/ijece.v2i6.1815